Integrin activating molecule-talin1 promotes skin fibrosis in systemic sclerosis - Xu, Dan; Yuan, Xiandun; Li, Zhaohua; Mu, Rong (Frontiers in Immunology, 2024)
Background: Integrin-dependent cell adhesion and migration play important roles in systemic sclerosis (SSc). The roles of integrin activating molecules including talins and kindlins, however, is unclear in SSc.We aimed to explore the function of integrin activating molecules in SSc.Methods: Transcriptome analysis of skin datasets of SSc patients was performed to explore the function of integrin-activating molecules including talin1, talin2, kindlin1, kindlin2 and kindlin3 in SSc. Expression of talin1 in skin tissue was assessed by multiplex immunohistochemistry staining. Levels of talin1 in serum were determined by ELISA. The effects of talin1 inhibition were analyzed in human dermal fibroblasts by real-time PCR, western blot and flow cytometry.We identified that talin1 appeared to be the primary integrin activating molecule involved in skin fibrosis of SSc. Talin1 was significantly upregulated and positively correlates with the modified Rodnan skin thickness score (mRSS) and the expression of pro-fibrotic biomarkers in the skin lesions of SSc patients. Further analyses revealed that talin1 is predominantly expressed in the dermal fibroblasts of SSc skin and promotes fibroblast activation and collagen production. Additionally, talin1 primarily exerts its effects through integrin β1 and β5 in SSc.Conclusions: Overexpressed talin1 is participated in skin fibrosis of SSc, and talin1 appears to be a potential new therapeutic target for SSc.